2011
DOI: 10.1007/978-3-642-20757-0_24
|View full text |Cite
|
Sign up to set email alerts
|

A Nash Bargaining Solution for Cooperative Network Formation Games

Abstract: Abstract. The Network Formation problem has received increasing attention in recent years. Previous works have addressed this problem considering almost exclusively networks designed by selfish users, which can be consistently suboptimal. This paper addresses the network formation issue using cooperative game theory, which permits to study ways to enforce and sustain cooperation among agents. Both the Nash bargaining solution and the Shapley value are widely applicable concepts for solving these games. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…In [21], the NBS is implemented to improve the fairness and efficiency of traffic engineering and server selection. In [22], network formation is addressed through the use of cooperative game theoretic tools such as the Shapley Value [1] and the NBS. There, it is numerically shown that the NBS permits to allocate costs fairly to users within a reasonable computation time.…”
Section: B Previous Workmentioning
confidence: 99%
“…In [21], the NBS is implemented to improve the fairness and efficiency of traffic engineering and server selection. In [22], network formation is addressed through the use of cooperative game theoretic tools such as the Shapley Value [1] and the NBS. There, it is numerically shown that the NBS permits to allocate costs fairly to users within a reasonable computation time.…”
Section: B Previous Workmentioning
confidence: 99%
“…The idea of using the Nash bargaining solution in the context of telecommunication networks has been considered in different networking scenarios [19,20,21,22,23,24].…”
Section: Related Workmentioning
confidence: 99%
“…Nahir et al [15] have considered similar NFG problems in directed graphs. Coalition and bilateral agreements between players in NFG and game-theory in general have been considered in [18], [5], [19], [2]. In order to evaluate "the goodness" of the equilibria, the prices of anarchy and stability [14], [20] have been used.…”
Section: Related Workmentioning
confidence: 99%